Exploring the link between financial globalization, financial development, human development and economic growth in China - Fergül Özgün (Financial Internet Quarterly, 2025)
The main objective of this study is to examine the relationship between globalization, financial development, human development and economic growth. The financial dimension of globalization, which is a multi-dimensional concept, is focused on, and the impact of financial globalization is investigated. The analysis was conducted in China. The KOF Globalization Index was used to represent financial globalization, the share of domestic loans given to the private sector in GDP was used to represent financial development, the Human Development Index was used to represent human development, and the GDP per capita value was used to represent economic growth. Because the stationarity levels of the variables were different from each other and there was a variable with I (2), the Toda-Yamamoto causality test was applied as a method. According to the results of the analysis covering the period 1990-2022, there is a causal relationship between the variables. There is bidirectional causality between financial globalization and economic growth. The causal relationship between human development and economic growth is also bi-directional. The causality relationship between financial development and economic growth is one-way, and the direction of causality is from economic growth to financial development. Economic growth should be encouraged to enhance financial development in China. Moreover, policies aimed at improving financial globalization and human development can be used to increase economic growth.
Keywords: E44; F15; J24; 330; Financial Globalization; Financial Development; Human Development; Economic Growth